On Road Vehicle Breakdown Help Assistance Web Application - C. S. Aravinthan; Dr. M. Hemalatha (International Journal of Scientific Research in Science and Technology, 2024)
The On Road Vehicle Breakdown Application proposes a solution to the common challenge faced by individuals experiencing vehicle breakdowns in remote areas. Unlike existing systems, this application connects registered users with certified mechanics through a secure platform. By offering a comprehensive database of approved mechanics, users can quickly locate assistance regardless of their location. This initiative aims to address the prevalent issue of inaccessible vehicle repair services in remote areas, ensuring prompt and reliable assistance for motorists in need.
Keywords: Vehicle Breakdowns; Remote Assistance; Certified Mechanics; Mobile Application; Roadside Support